Phenotype of Innate Immune Cells in Uveitis Associated with Axial Spondyloarthritis- and Juvenile Idiopathic Arthritis-associated Uveitis. (18th August 2021) - Kasper, Maren; Walscheid, Karoline; Laffer, Björn; Bauer, Dirk; Busch, Martin; Loser, Karin; Vogl, Thomas; Langmann, Thomas; Ganser, Gerd; Rath, Thomas; Heiligenhaus, Arnd
ABSTRACT: Purpose : To analyze circulating immune cells in patients with anterior uveitis (AU) associated to axial spondyloarthritis (SpA), or juvenile idiopathic arthritis (JIA). Methods : Venous blood samples were collected from healthy controls (n = 16), and either SpA (n = 19) or JIA (n = 23) patients with associated anterior uveitis (AU) during active flare, or after ≥3 months of inactivity. Frequencies of CD56 +, MHC-I +, and S100A9 + monocytes, CCR7 + dendritic cells, CD56 +dim natural killer (NK) cells and CD3 + CD56 bright T-cells were analyzed via flow cytometry. Serum S100A8/A9 levels were determined via ELISA. Results : SpA patients showed a reduced frequency of CD56 +dim NK cells during uveitis activity, a constitutively activated monocyte phenotype, and elevated S100A8/A9 serum levels. In contrast, JIAU patients showed elevated frequencies of CD56 + monocytes and CCR7 + DC. Conclusion : Phenotype of peripheral immune cells differ between patients, probably contributing to different courses of acute onset AU in SpA and insidious onset AU in JIAU patients. Abbreviations : AU: anterior uveitis, AR: arthritis, JIA: juvenile idiopathic arthritis, SpA: axial spondyloarthritis